Morphological Characteristics of Bioactive Compounds on Api-Api Mangrove Leaves Extract (Avicennia marina) Based on Leaves Age - Muhamad Zaky Zamani; Arief Prajitno; Mohamad Fadjar (Research Journal of Life Science, 2019)
Api-api leaves A. marina has a variety of active compounds that have been confirmed to too wordy be used as antibacterial agents, where harvesting of mangrove leaves is carried out at the location of Betoyoguci Gresik and differentiated by age, this age differentiation is based on morphological characteristics because it has color differences significant. Where age is one of the factors that affect the level of active compounds found in leaves. Extraction results of mangrove api-api gave different yield levels in each age level. The order of yields from the largest to the smallest is the old leaves 3%, fall 2.86% and young leaves 2.04%. Whereas based on phytochemical test the best extracts were obtained, namely old leaves, fall leaves and young leaves, FT-IR results with 10 detected absorption files which indicate the presence of functional group characteristics that can be used as an illustration of the presence of antibacterial compounds. In the LC-MS test with identification of several molecular weights which indicated a signal derivative of flavonoid compounds in the form of dihydroquercetin, quercetin-3-O-β-D-xylopyranoside, quercetin-3-O-β-D-galactopyranoside, isohametin-7-O-pentoside and routine, and derivatives of detected alkaloid compounds in the form of berberine and papaverine.